The cytological analysis of crossing over in armadillos supports the existence of a phylogenetic component of recombination rates in mammals - Luis Francisco Rossi; María Inés Pigozzi (PLoS ONE, 2025)
In mammals rates of recombination are well predicted by the phylogenetic relationship between species, with lower recombination rates in more basal clades. In this regard, there is currently insufficient evidence for Xenarthra, one of the earliest branches of eutherian mammals. Here we estimated the average recombination rates in four species of armadillos (Cingulata, Xenarthra) using immunodetection of the protein MLH1, a reporter of reciprocal recombination, in pachytene. The recombination rates of the examined species are strikingly similar; despite the fact that they split more than 40 million years ago, suggesting that this may be a conserved trait in other Xenarthra. We provide evidence that armadillos have lower recombination rates than the average for eutherian mammals, and that they approach those of rodents more closely than those of early mammalian clades like Afrotheria.